The Effect of The Nursing Image Used in the Red Crescent and Child Welfare Agency Stamps Between 1912-1958 on the Social Perception of Women: A Review - Nesrin Özdil; Bahadır Elal; Ülkü Baykal (Sağlık ve Hemşirelik Yönetimi Dergisi, 2022)
Introduction: Nursing and its image were introduced to Turkish society for the first time with stamps by the government. Aim: This study aims to investigate the nurse figures and the reasons for their use, how the nurse image is reflected in society, and what discourses are intended to be communicated domestically and internationally on the stamps commemorating the end of the Ottoman Empire and the beginning of the Republic of Turkey. Method: Nurse figures on the Red Crescent and Child Welfare Agency compassion stamps, which were used together with postage stamps between 1912-1958, are analyzed with the document analysis method and content analysis and critical discourse analysis design. Results: It can be seen that the woman was represented in an official document as a nurse, side by side and equal with a man, for the first time by the state during the era when stamps were issued. Conclusion: It has been seen that the perception of women in the world and society is conveyed with these stamps as an individual who has a profession and participates in social and economic life, the importance is given to nursing, the efforts to encourage the profession, the emotion and value of institutions such as power, respect, compassion, and trust are conveyed with nurse figures on the stamps.